Mitochondrial DNA copy number in cumulus cells is a strong predictor of obtaining good-quality embryos after IVF - Ogino, Mai (J Assist Reprod Genet, 2016)
PURPOSE: The aim of this study was to establish a simple tool to predict good-quality embryos in in vitro fertilization (IVF) by using cumulus cells (CCs) or peripheral blood cells (PBCs). METHODS: Mitochondrial DNA was extracted from CCs and PBCs in patients undergoing IVF. Using real-time polymerase chain reaction, mtDNA copy number in a single cell was calculated. Embryo quality was assessed when it was transferred or frozen. RESULTS: CCs were obtained from 60 oocyte cumulus-cell complexes (OCCCs) in 30 women, and PBCs were collected from 18 women. For the 30 women in the study, the median age was 37 years old (range, 24–43), and the mean body mass index was 21.4 (standard error, 2.0). mtDNA content of CCs and PBCs was highly correlated (Pearson’s r = 0.900, p < 0.0001). The median mtDNA content of CCs for good- and poor-quality embryos was 140 and 57, respectively (p < 0.0001). The median mtDNA content of PBCs for good- and poor-quality embryos was 36 and 13, respectively (p = 0.604). The logistic regression model indicated that mtDNA content in CCs was the only parameter that predicted good-quality embryos (p = 0.020). The receiver operating characteristic curve for obtaining good-quality embryos by mtDNA copy number in CCs had an area under the curve of 0.823, and using a threshold of 86, positive and negative predictive values were 84.4 and 82.1 %, respectively. CONCLUSIONS: The determination of mtDNA content in CCs can be used to predict good-quality embryos.